Β‐Adrenoceptor signaling regulates proliferation and contraction of human bladder smooth muscle cells under pathological hydrostatic pressure. Issue 10 (3rd June 2019) - Lai, Junyu; Ai, Jianzhong; Luo, Deyi; Jin, Tao; Liao, Banghua; Zhou, Liang; Feng, Shijian; Jin, Xi; Li, Hong; Wang, Kunjie
Abstract: Background: Partial bladder outlet obstruction (PBOO) promotes bladder detrusor hyperplasia, increases bladder pressure, and decreases bladder compliance. To extensively explore its underlying mechanism, our study aimed to investigate the effect of pathological hydrostatic pressure on human bladder smooth muscle cell (hBSMC) proliferation and contraction through β‐adrenoceptor (ADRB) signaling in vitro. Methods: hBSMCs were subjected to pathological hydrostatic pressure (100 cm H2 O) to investigate the effect of ADRBs on the proliferation and contraction of hBSMCs treated with its agonists and/or antagonists. Results: Firstly, exposure to 100 cm H2 O hydrostatic pressure significantly upregulated the expression of α‐smooth muscle actin (α‐SMA) in hBSMCs at 6 hours, and promoted cell proliferation at 24 hours. When subjected to hydrostatic pressure alone, hBSMCs treated with ADRB2 and ADRB3 agonists for 6 hours inhibited α‐SMA expression compared with untreated cells. By contrast, hBSMCs treated with ADRB2 agonists for 24 hours suppressed cell proliferation compared with untreated cells. The two classical pathways of ADRB, protein kinase A (PKA), and exchange factor directly activated by cAMP (EPAC) inhibited the contraction of hBSMCs under hydrostatic pressure via regulating mothers against decapentaplegic homolog 2 (SMAD2) activity. The proliferation of hBSMCs was mainly regulated by the EPAC pathway through extracellular signal‐regulated kinase 1/2 (ERK1/2) activity. Conclusion: The contraction of hBSMCs under hydrostatic pressure was regulated by ADRB2 and ADRB3 via the PKA/EPAC‐SMAD2 pathway, and the proliferation of hBSMCs was regulated by ADRB2 via the EPAC‐ERK1/2 pathway. Compared with ADRB3, ADRB2 played a predominant role under pathological hydrostatic pressure. These findings markedly uncovered the underlying mechanism of ADRBs in PBOO and provided new insights into the efficient treatment of patients with PBOO. Abstract : The contraction of hBSMCs under hydrostatic pressure was regulated by ADRB2 and ADRB3 via the PKA/EPAC‐SMAD2 pathway, and the proliferation of hBSMCs was regulated by ADRB2 via the EPAC‐ERK1/2 pathway. Compared with ADRB3, ADRB2 played a predominant role under pathological hydrostatic pressure.